The relationship between responsible leadership and individual performance: Affective commitment and individual creativity as sequential mediators - Simões, L. M. (2023)
In the last decade, responsible leadership (RL) has been gaining more interest in terms of research and practice. However, empirical evidence on its impacts on organizational and individual outcomes needs to be further explored (Haque et al., 2018, 2021; Waldman et al., 2020). RL is described as a way to build and maintain positive relationships with the organization's internal and external stakeholders, as well as responsibly coordinate actions to achieve a shared and meaningful business vision that contributes to sustainable value creation. and positive changes (Maak & Pless, 2006). As such, its potential positive outcomes from different stakeholders’ perspectives are diverse. In what concerns employees, previous research found a direct and significant relationship between RL and individual performance (Lin et al., 2020; Simões & Duarte, 2021). That is, the adoption of a responsible leadership style seems to foster better individual performance. However, is not clear how the relationship is established and the cited authors pointed out the necessity to explore possible mediating and moderating variables. Addressing this research gap, the current study explores the potential intervention of affective commitment and individual creativity as sequential mediators. Haque et al. (2018, 2021), Mousa (2017), and Simões and Duarte (2021) found a positive relationship between RL and affective commitment. Furthermore, Castro-González et al (2019) and Simões et al. (2021), also found a positive significant relationship between RL and individual creativity. The relationship between affective commitment and individual creativity has also been established (Leung & Lin, 2022; Ribeiro et al., 2020). Thus, affective commitment and individual creativity could emerge as potential psychological mechanisms that help explain the direct relationship between RL and individual performance. A quantitative correlational study based on an electronic survey was conducted, collecting data from 260 employees from different organizations, through a non-probabilistic convenience sample. The questionnaire was based on self-report instruments developed to measure RL, affective commitment, individual creativity, and individual performance. All instruments revealed adequate reliability, as well as convergent and discriminant validity in the present sample. The results from multiple regression analysis using PROCESS macro for SPSS indicated a positive and significant relationship between RL and individual performance. The indirect effect of affective commitment on the relationship between RL and individual performance was also significant, but the same did not happen with the indirect effect of individual creativity. Regarding the third indirect effect of the sequential effect of affective commitment and individual creativity at work on the relationship between RL and individual performance, it was positive and statistically significant. This indicates that RL contributes to strengthening the employee's affective commitment to the organization, which increases individual creativity at work, which, in turn, reinforces his/her individual performance at work. The model explains 32% of the variation in individual performance. This means that both affective commitment and creativity, when combined, can help explain the relationship between the main variables of the model, indicating that the individuals' affective bond with the organization and their individual creativity are important variables that need to be considered by a responsible leader in order to influence desired results of their employees, such as improved individual performance. As for the originality of this study, the literature had already found some evidence of the links between the variables in this research model but combining them on a sequential mediation offers a new perspective on the psychosocial process whereby the relationships between constructs are established. In sum, this research suggests that RL can have a positive impact on the individual and, later, on an organizational level. Responsible leader presents themselves as a leader that can better communicate with their employees, build trusting relationships as well as integrate them into the decision-making process. These characteristics can then contribute to employees’ better work experiences, fostering their affective bond to the organization, their tendency to provide more useful and new ideas regarding work processes and results, and, thereby, improve their individual work performance.